On the particularities of the forced vibration of the hydro-elastic system consisting of a moving elastic plate, compressible viscous fluid and rigid wall - Akbarov, Surkay D.; Panakhlia, Panakh G. (TECHNO-PRESS, 2017)
This paper studies the particularities of the forced vibration of the hydro-elastic system consisting of a moving elastic plate, compressible viscous fluid and rigid wall. This study is made by employing the discrete-analytical solution method proposed in the paper by the authors (Akbarov and Panakhli (2015)). It is assumed that in the initial state the fluid flow is caused by the axial movement of the plate and the additional lineally-located time-harmonic forces act on the plate and these forces cause additional flow field in the fluid and a stress-strain state in the plate. The stress-strain state in the plate is described by utilizing the exact equations and relations of the linear elastodynamics. However, the additional fluid flow field is described with linearized Navier-Stokes equations for a compressible viscous fluid. Numerical results related to the influence of the problem parameters on the frequency response of the normal stress acting on the plate fluid interface plane and fluid flow velocity on this plane are presented and discussed. In this discussion, attention is focused on the influence of the initial plate axial moving velocity on these responses. At the same, it is established that as a result of the plate moving a resonance type of phenomenon can take place under forced vibration of the system. Moreover, numerical results regarding the influence of the fluid compressibility on these responses are also presented and discussed.
Keywords: compressible viscous fluid; elastic plate; frequency response; critical frequency; moving plate; forced vibration; STABILITY; VISCOSITY; WAVES; LAYER; Mechanics